CircRNF121 knockdown suppresses the progression of cervical cancer by regulating miR‐153‐3p/ATF2 axis and wnt/β‐catenin pathway. Issue 3 (3rd January 2022) - Wang, Qi; Xu, Bai; Liu, Haiping; Wang, Dongwei; Liu, Siyang; He, Chi; Feng, Xiaona; Wang, Limin
Abstract: Cervical cancer (CC) is a common malignancy in gynecology. Emerging evidence has demonstrated that circular RNAs (circRNAs) act as vital mediators in CC. However, the roles of circRNA ring finger protein 121 (circRNF121) in CC are largely unknown. Herein, we focused on the exact function and underlying mechanism of circRNF121 in CC development. Our results showed that circRNF121 was highly expressed in CC tissues and cells. Knockdown of circRNF121 suppressed cell growth, metastasis, epithelial‐mesenchymal transition (EMT), autophagy, and wnt/β‐catenin pathway in CC cells in vitro and blocked tumor formation in vivo. For mechanism investigation, circRNF121 could affect activating transcription factor 2 (ATF2) expression by decoying miR‐153‐3p, thereby accelerating CC cell development. In conclusion, circRNF121 exerted the tumor‐suppressive role in CC progression by altering miR‐153‐3p/ATF2 axis. These results suggested that circRNF121 might be a possible circ‐targeted therapy for patients with CC.